The factors influencing postoperative efficacy of anterior clinoidal meningioma treatment and an analysis of best-suited surgical strategies - Chen, Li-Hua; Xia, Yong; Wei, Fan; Sun, Kai; Huang, Hong-Zhi; Xu, Ru-Xiang (Frontiers in Neurology, 2023)
Objective: To explore the influence of the type of anterior clinoidal meningioma on surgical strategy planning, surgical approach selection, and postoperative efficacy. Patients and Methods: We conducted a retrospective analysis of the clinical data of 63 cases, including data on visual function, extent of tumor resection, and postoperative follow-up. Grade I and II approaches were selected according to the type of tumor. A univariate analysis of the factors influencing the extent of tumor resection, postoperative visual function, and postoperative relapse and complications was conducted. Results: Simpson Grade I–II total resection was seen in 48 cases (76.2%), with an overall relapse/progression rate of 12.7%. The tumor type and texture and the relationship between the tumors and adjacent structures were the main factors influencing total tumor resection (P < 0.01). The overall postoperative visual acuity improvement, stabilization rate, and deterioration rate were 76.2%, 15.9%, and 7.9%, respectively. Postoperative visual acuity level was significantly correlated with preoperative visual acuity level and tumor type (P < 0.01). Conclusions: Determining the type of tumor at a preoperative level and whether the optic canal and cavernous sinus are invaded can aid in the planning of detailed individualized surgical strategies.